Mining the Technical Skills of Open Source Developers - Montandon, João Eduardo; Valente, Marco Túlio (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2022: Anais do XXXV Concurso de Teses e Dissertações, 2022)
Software has "eaten the world" as we witness the rise of companies whose business model is totally centered on software. The successful implementation of these systems heavily depends on the quality and expertise of their software development teams. However, software-based companies are facing an increasing software developers shortage issue. On the one hand, technical recruiters are increasingly relying on the information provided by Social Coding Platforms (SCPs)—e.g., GitHub, Stack Overflow, etc—to prospect new talent. On the other hand, the large volume of data available force job recruiters to only assess superficial information of their candidates. In order to tackle this problem, we described in the thesis an extensive investigation of methods and techniques to identify the technical skills of software developers based on their activity in SCPs. We organized the thesis in three major working units, where we first investigated the most demanded technical and soft skills under the eyes of IT companies, and then assessed developers' technical skills from deep and broad prespectives. These studies resulted in contributions to both research and industrial communities.